As relações entre ciência, tecnologia e sociedade no ensino de ciências: o que diz a prática docente - Silva, Selma Gonzaga (2002)
The objective of this study is to understand how the relationship between Science, Technology and Society is being approached in the teaching of Science. In order to achieve this, the pedagogical practice of three Eighth Grade Science teachers was analysed with the objective of searching for inferences that relate to their conceptions about Science and Technology and the relationship between Science/Technology/Society, as well as verifying the knowledge demonstrated by the teachers respecting the tendency toward STS in the teaching of this subject. Therefore, the fírst move was to employ a methodological course linked to the ethnographic research field, beginning with direct class observation. The teaching material utilized by the teachers participating in the study and the other documents analysed were only examined when necessary, in order to better understand the facts observed. Next, semi-structured interviews were conducted with the teachers, right after attending their classes. Finally, data analysis was made, taking the following parameters into consideration: a) articulation of the contents with student reality; b) treatment of social themes; c) the treating of Science as a human activity, historically contextualized; d) the search for development of judging atitudes, decision-making capacity. Data analysis made it possible to conclude that the approach of social issues related to Science and Technology becomes apparent in teaching practices, but at a severely restricted levei, with a scope limited to its pertinence to using or not certain technologies or technological products, based on underlying scientific knowledge. Analysis of this type of orientation in the light of what is proposed as Citizen preparation, that is, preparing students for social participation, as well as indicating the necessary transformations for making decisions on social issues that involve aspects referring to Scientific/Technological developments, verifíed that the program developed in schools under the perspective of STS is very limited and non-critical.